Empowerment of Business Development Centers of State Islamic Religious Universities: Recommendations for Functional Autonomy and Strategic Partnership Policies - Zikrawahyu (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This policy paper analyzes the failure of the Business Development Center (Pusbis) of the State Islamic Religious College (PTKIN) as a Public Service Agency (BLU) to optimize non-academic revenue, a crucial issue for the institution's financial independence. The analysis indicates that the primary root cause is regulations that are not adaptive to market dynamics and tend to focus on administrative control rather than commercial efficiency. This is exacerbated by a risk-averse institutional culture and limited functional autonomy. The approach used is a systematic policy problem analysis to identify root causes and their implications. Identified problems are prioritized using the Urgency, Seriousness, Growth (USG) framework, which confirms that irrelevant regulations are the most pressing issue. Next, three policy alternatives—the issuance of a Ministerial Regulation (PMA) on Strategic Partnerships, a Rector's Decree on Functional Autonomy, and a Rector's Decree on Asset Utilization—are comparatively evaluated. This assessment is conducted using William N. Dunn's scoring of policy alternatives based on the criteria of effectiveness, efficiency, adequacy, equity, and responsiveness. The results indicate that the issuance of a PMA on Strategic Partnerships is the most effective alternative. This policy is recommended to provide a clear legal umbrella, simplify bureaucracy, and facilitate productive collaboration that will ultimately empower Pusbis and accelerate the achievement of financial independence of PTKIN.